Corporate Governance and Earnings Management: Evidence from listed Malaysian Firms - Mohamad, Shafi (International Journal of Psychosocial Rehabilitation, 2020)
This paper combines the twin aspects of corporate governance and earnings management by providing deeper insights into the role played by the government as a major stakeholder of Government-Linked Companies (GLCs) in Malaysia. In 2004, the Malaysian government embarked on a transformation exercise for all GLCs in the country. The program was designed to strengthen and deepen the mechanisms of corporate governance and anchor best practices from within. The Malaysian government undertook this exercise as part of its efforts to enhance the effectiveness of Boards of state-owned enterprises. The aims and objectives of this paper therefore are to give detail insights into the corporate governance reforms and provide an in-depth understanding of the impact of corporate governance mechanisms deriving from these transformation programs. In order to provide detailed insights regarding this aspect, our study includes both pre and post transformation data and concludes whether these transformational policies and earnings management activities have contributed to any sort of lingering after effects. This study also provides suggestions for any further policy improvements if necessary. This study found that there was a reported increase in earnings management activities during the post transformation period. The study also found that post transformation there was little or no impact resulting from corporate governance measures to subdue earnings management activities, on the other hand, both the leadership structure and frequency of board meetings appeared to have a significant impact. The official get-togethers and separation of functions between the CEO and Chairperson in the organisation appeared to adversely influence and benefit the board respectively during the post-transformation period whereas the association does not appear to hold in the pre-transformation period. Even though our study demonstrated a positive uplift from enhanced corporate governance mechanisms in GLCs, further studies to identify the specific factors that contributed to this feel good factor would appear to be warranted.